Qualitätsmanagement in der notfallmedizinischen Versorgung von Patienten mit schwerem Schädel-Hirn-Trauma = Quality management of patients with severe traumatic brain injury in emergency medicine - Viergutz, Tim; Schmittner, Marc; Weiß, Christel (Notfall & Rettungsmedizin, 2015)
Background: The aim of this study was to evaluate the current quality of preclinical care of patients with severe traumatic brain injury by emergency physicians from the University Hospital Mannheim, Germany. Specifically, this study investigated whether the guidelines for preclinical care of patients with traumatic head injury were followed. Methods: This study retrospectively investigated patients with severe traumatic brain injury who were treated out of hospital by an emergency physician from the University Hospital Mannheim between 1 January 2005 and 1 August 2012. Included were patients with a traumatic brain injury who initially presented a Glasgow Coma Scale (GCS) < 9, a National Advisory Committee for Aeronautics (NACA) Score > 3, and were 16 years and older. Results: A total of 51 patients with severe traumatic brain injury (GCS < 9) were treated by emergency physicians of the University Hospital Mannheim. Remarkable was that only 14 % of these patients received all the recommended preclinical treatments. The majority of the patients with severe traumatic brain injury as the suspected diagnosis (47 out of 51) were transported to the University Hospital Mannheim. In 29 out of those 47 patients (62 %), the suspected diagnosis was verified in the following clinical workup, whereby 14 of the 29 patients died during their hospitalization as a consequence of their head injury. Conclusions: The care for patients with severe traumatic brain injury is complex and demanding. In this study, especially the easily applied, but nevertheless fundamental treatments and diagnostics like determining blood sugar in patients with reduced vigilance, correct positioning of the patient, and end-expiratory measurement of CO2 in intubated patients were only unsatisfactorily performed.